Pengaruh Lingkungan Kerja, Beban Kerja, dan Motivasi Kerja terhadap Kinerja Karyawan pada PT. Yudhistira Ghalia Indonesia - Yunisa Ogda; Sudarijati Sudarijati; Ismartaya Ismartaya (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the simultaneous and partial effects of work environment, workload, and work motivation on employee performance at PT Yudhistira Ghalia Indonesia. This research uses a quantitative approach based on both primary and secondary data. The sampling technique applied is simple random sampling, with a total of 100 respondents. The analytical methods used include descriptive-verificative analysis and multiple linear regression analysis. The results of the study show that (1) simultaneously, the work environment, workload, and work motivation have a positive and significant effect on employee performance; (2) partially, the work environment has a positive and significant effect on employee performance; (3) partially, workload has a negative and significant effect on employee performance; and (4) partially, work motivation has a positive and significant effect on employee performance.